Method for synthesizing lead sulfide quantum dots through mediation of extracellular polymeric substances
Extract extracellular polymers through ammonium salt stress/induce and cultivate desulfurization vanguard, and use it to mediate the synthetic leader -sulfide quantum dot to solve the problem of using toxic reagents and harsh response conditions in existing technologies. Environmentally friendly leading quantum synthesis has excellent physical and chemical properties.
Patent Information
- Application Number
- CN202411497260.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
The prior art requires the use of acid and alkali and toxic reagents when preparing lead sulfide quantum dots, and the reaction conditions are harsh, resulting in high production costs and environmental pollution.
Cultivate the cultivation of desulfurization and desulfurization submorous sulfur submori in ammonium salt, extract extracellular polymers, and use it to media the synthetic sulfide quantum dot, remove excess lead ions by adsorbing and dialysis steps, and finally add sulfur ions solution Quantum dot.
Under mild conditions, high -efficiency synthetic sulfide quantum dots have excellent performance of crystal stability, larger than surface area, uniform particle size distribution, and high crystallization, and are environmentally friendly and low -cost.
Smart Images

Figure CN119370884A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductor nanomaterials, and in particular relates to a method for synthesizing lead sulfide quantum dots mediated by extracellular polymers. Background Art
[0002] Lead sulfide quantum dots have the characteristics of adjustable band gap width and high stability. They have attracted widespread attention from scholars at home and abroad and are widely used in optoelectronic devices such as infrared detectors, light-emitting diodes, field-effect transistors and solar cells. In medicine, quantum dots with different luminescent wavelengths are used to make fluorescent labels, which become nanobarcodes for biological detection.
[0003] At present, the physical-chemical method is the main synthesis method of quantum dot semiconductors. It can prepare lead sulfide quantum dots of different particle sizes and has certain advantages in production speed and capacity. However, this method requires the use of acids, alkalis, toxic reagents, and high pressure, temperature and other reaction conditions, and requires high capital costs and more energy. In order to solve these problems, researchers have explored the microbial synthesis of semiconductor metal sulfide quantum dots. Compared with traditional synthesis methods, biosynthesized nanoparticles have the advantages of high efficiency and environmental protection, low cost, high compatibility, mild and controllable reaction conditions, and no need to add stabilizers. In addition, this method is characterized by using low-toxic sodium sulfide as a precursor for the preparation of lead sulfide quantum dots, which is a green synthesis method.
[0004] Intracellular and extracellular are two pathways for the biosynthesis of quantum dots. In the process involving sulfate-reducing bacteria, sulfide is generated intracellularly through sulfate dissimilatory reduction and / or assimilatory reduction, but this method is difficult to prepare large-scale quantum dots. Extracellular synthesis has greater application potential in the large-scale production of quantum dots. Therefore, if sodium sulfide can be used as a precursor to synthesize lead sulfide quantum dots in bacterial extracellular biosynthesis, it will surely show important application value in promoting the advancement of heavy metal wastewater treatment technology and realizing high-value utilization of resources. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the present invention proposes a method for synthesizing lead sulfide quantum dots, using ammonium salts (such as ammonium chloride, etc.) as a stress / induction factor to promote the secretion of extracellular polymers by Desulfovibrio desulfuricans subspecies, and then utilizing its extracellular polymers to mediate the synthesis of lead sulfide quantum dots. The resulting product has the advantages of stable crystal phase, large specific surface area, uniform particle size distribution, high crystallinity, etc.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] The present invention provides a method for synthesizing lead sulfide quantum dots mediated by extracellular polymers, the method comprising the following steps:
[0008] S1, culture Desulfovibrio desulfuricans subsp. desulfuricans by ammonium stress / induction, and extract extracellular polymeric substances (EPS);
[0009] S2, mixing the extracellular polymers of S1 with the lead ion solution, and performing dialysis after sufficient adsorption to remove excess lead ions;
[0010] S3. After dialysis, sulfide ion solution is added, and the synthesized lead sulfide quantum dots are collected by centrifugation after standing.
[0011] The present invention utilizes the important template role of extracellular polymers in the process of biosynthesizing lead sulfide quantum dots, and has the advantages of simple operation, high efficiency, environmental protection, low cost, good reproducibility, etc. At the same time, the production of extracellular polymers is significantly increased by using ammonium salt stress / induction to cultivate desulfurization Vibrio desulfuricans subspecies, thereby increasing the adsorption of heavy metal lead and the production of lead sulfide quantum dots. In addition, the lead sulfide quantum dots prepared by the method of the present invention have excellent properties such as stable crystal phase, large specific surface area, uniform particle size distribution, and high crystallinity.
[0012] Preferably, S1 specifically comprises: inoculating Desulfovibrio desulfuricans subsp. desulfuricans into a Starkey medium containing ammonium salts, and extracting the extracellular polymers produced by Desulfovibrio desulfuricans subsp. desulfuricans after stress / induced culture.
[0013] More preferably, the concentration of the ammonium salt in the Starkey medium is 1.2-2.4 g / L, and the ammonium salt includes at least one of ammonium chloride, ammonium oxalate and ammonium bicarbonate. Further, the ammonium salt is ammonium chloride.
[0014] According to research, the output of extracellular polymers was the highest when the concentration of added ammonium chloride was 2.0g / L, reaching 645.41mg / g; the yield of lead sulfide quantum dots synthesized under the mediation of extracellular polymers at this concentration was 17.45g / g EPS, an increase of 51.74% compared with before induction; the yield was also the highest, with the quantum dot yield per unit strain reaching 12.50g / g biomass, an increase of 357.88% compared with before stress / induction.
[0015] More preferably, the stress / induction culture is carried out in the form of shaking culture, wherein the shaking culture temperature is 25 to 35° C., the time is 60 to 84 h, and the shaking speed is 120 to 180 r / min.
[0016] More preferably, the Desulfovibrio desulfuricans subsp. desulfuricans is first prepared into a Desulfovibrio desulfuricans subsp. desulfuricans bacterial suspension before inoculation, and the Desulfovibrio desulfuricans subsp. desulfuricans bacterial suspension is inoculated into Starkey culture medium at a volume fraction of 5% to 15%.
[0017] Furthermore, the preparation method of the Desulfovibrio desulfuricans subspecies bacterial suspension is as follows: the purchased Desulfovibrio desulfuricans subspecies is inoculated into Starkey culture medium at a volume fraction of 3% to 7%, and activated by shaking at 28°C to 32°C for 36h to 60h to obtain the Desulfovibrio desulfuricans subspecies bacterial suspension.
[0018] More preferably, the extraction of extracellular polymers comprises removing the culture medium and ammonium salts, and then removing the bacterial cells to obtain the extracellular polymers.
[0019] Furthermore, the method for removing the culture medium and ammonium salt is as follows: the treated liquid after ammonium salt stress / induction culture is placed at 3-5°C and centrifuged at a speed of 7000-9000r / min for 8-12min, for a total of 2-4 times, and after each centrifugation, it is washed with a salt solution with a mass percentage of 0.8-1.0% to wash away the residual culture medium and ammonium salt on the bacteria. The method for removing bacteria adopts the NaOH method: add a salt solution with a mass percentage of 0.8-1.0% to the treatment liquid from which the culture medium and ammonium salt are removed, and add 0.25-0.75mL of 0.8-1.2mol / L sodium hydroxide, and let it stand for 2-4h at 3-5°C after sufficient mixing, then centrifuge 1-2 times at a centrifugal speed of 10000-14000r / min and a centrifugal time of 15-25min, collect the supernatant, filter it with a 0.22-0.45μm cellulose acetate filter membrane, and then place it in a 4000Da dialysis bag for dialyzing for 12-36h to remove the bacteria.
[0020] Preferably, in S2, the mass volume ratio of the extracellular polymer to the lead ion solution is 1:1-5.
[0021] Preferably, in S2, the adsorption is carried out on a shaker at a shaking speed of 120-180 r / min at 25-35°C for 1-3 hours.
[0022] Preferably, in terms of the dosage of the sulfide ion solution and the lead ion solution, the molar ratio of the sulfide ions to the lead ions is 1:2-5.
[0023] Preferably, the concentration of the aqueous solution of lead ions is 0.01-0.2 mol / L; the concentration of the aqueous solution of sulfide ions is 0.01-0.05 mol / L.
[0024] Preferably, in the lead ion solution, the source of lead ions includes at least one of Pb(NO3)2, PbCl2 and PbSO4; and the source of sulfide ions in the sulfide ion solution is sodium sulfide.
[0025] Preferably, in S3, the standing time is not less than 30 min.
[0026] The invention also provides lead sulfide quantum dots synthesized by the above method.
[0027] According to research, the lead sulfide quantum dots synthesized by the method of the present invention have a larger specific surface area and a smaller average pore size than the lead sulfide synthesized by chemical synthesis, indicating that the lead sulfide quantum dots synthesized under the mediation of extracellular polymers have more active sites and stronger adsorption capacity, proving that the synthesis mediated by extracellular polymers promotes the catalytic performance of lead sulfide quantum dots.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The present invention discloses a method for synthesizing lead sulfide quantum dots mediated by extracellular polymers, which comprises the following steps: culturing desulfurization subspecies of Vibrio desulfuricans by ammonium salt stress / induction, extracting extracellular polymers (EPS), then mixing and adsorbing the EPS with a solution containing lead ions and performing dialysis, adding a solution containing sulfur ions after dialysis, and obtaining lead sulfide quantum dots after standing and centrifugation. The present invention utilizes the important template role of extracellular polymers in the process of biosynthesis of lead sulfide quantum dots, and has the advantages of simple operation, high efficiency and environmental protection, low cost, and good reproducibility; at the same time, the desulfurization subspecies of Vibrio desulfuricans is cultured by stress / induction of ammonium salts (such as ammonium chloride, etc.), which significantly increases the yield of extracellular polymers, thereby increasing the adsorption of heavy metal lead and the yield and yield of lead sulfide quantum dots. In addition, the lead sulfide quantum dots prepared by the present invention have excellent properties such as stable crystal phase, large specific surface area, uniform particle size distribution, and high crystallinity. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The main components of extracellular polymers produced by Desulfovibrio desulfuricans subsp. desulfuricans before and after ammonium chloride, ammonium oxalate and ammonium bicarbonate stress / induction;
[0031] Figure 2 The yield diagram of the extracellular polymer-mediated synthesis of lead sulfide quantum dots produced by Desulfovibrio desulfuricans subsp. desulfuricans before and after ammonium chloride, ammonium oxalate and ammonium bicarbonate stress / induction;
[0032] Figure 3 Fourier transform infrared spectra of lead sulfide quantum dots synthesized by extracellular polymers mediated by desulfuricans desulfuricans subsp. before and after stress / induction of ammonium chloride, ammonium oxalate and ammonium bicarbonate (Control-PbS is lead sulfide quantum dots synthesized by extracellular polymers mediated before stress);
[0033] Figure 4 High-resolution transmission electron microscopy, lattice spacing and particle size distribution of lead sulfide quantum dots produced by extracellular polymer-mediated synthesis of Vibrio desulfuricans under ammonium chloride stress / induction;
[0034] Figure 5The selected area electron diffraction pattern of lead sulfide quantum dots synthesized by extracellular polymers mediated by Desulfovibrio desulfuricans subsp. desulfuricans before and after ammonium chloride stress / induction (Control-PbS is lead sulfide quantum dots synthesized by extracellular polymers mediated before stress);
[0035] Figure 6 Nitrogen adsorption / desorption curves and pore size distribution of lead sulfide quantum dots synthesized by extracellular polymers mediated by desulfurizing Vibrio desulfuricans and chemically synthesized lead sulfide before and after ammonium chloride stress / induction (NH4Cl-PbS is lead sulfide quantum dots synthesized by extracellular polymers mediated after stress, Control-PbS is lead sulfide quantum dots synthesized by extracellular polymers mediated before stress, and None-PbS is chemically synthesized lead sulfide). DETAILED DESCRIPTION
[0036] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0037] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0038] Example 1: Ammonium stress / induction of Desulfovibrio desulfuricans subsp. desulfuricans to produce extracellular polymers
[0039] The sulfate-reducing bacteria Desulfovibrio desulfuricans subsp. desulfuricans used in this embodiment is a Gram-negative anaerobic bacterium purchased from the China General Microbiological Culture Collection Center (the collection number of the strain is CGMCC 1.3469). The strain culture was activated by Starkey medium (K2HPO4 0.50 g, NH4Cl 1.00 g, Na2SO4 1.00 g, CaCl2·2H2O 0.10 g, MgSO4·7H2O 2.00 g, 60% DL-sodium lactate 2.50 g, yeast extract 1.00 g, pH = 7, sterilized in a 121°C autoclave for 20 min), and then stored at -80°C with a volume ratio of glycerol: bacterial solution = 1:4. Among them, the specific preparation method of the extracellular polymer comprises the following steps:
[0040] (1) Activation culture: The Desulfovibrio desulfuricans subsp. desulfuricans culture medium stored at -80°C was taken out, thawed to room temperature and inoculated into 95 mL of Starkey medium at 5% (volume fraction) under sterile conditions, and then 1 mL of 10.00 g / L sterilized ascorbic acid solution was added. Nitrogen was blown continuously for 1 min, and the medium was sealed with a sealing film and tin foil. After activation culture at a constant temperature (30°C) and shaking (150 r / min) for 48 h, a Desulfovibrio desulfuricans subsp. desulfuricans suspension was obtained.
[0041] (2) Stress / induction culture: Under sterile conditions, a suspension of Desulfovibrio desulfuricans subsp. desulfuricans was inoculated at 10% (volume fraction) in 90 mL of Starkey medium, and 1 mL of 10.00 g / L sterilized ascorbic acid solution was added. Then, under sterile conditions, 2 mL of 100.00 g / L sterilized ammonium chloride solution was injected into the Starkey medium to a concentration of 2.0 g / L. Nitrogen was blown continuously for 1 min. After sealing with a sealing film and tin foil, the medium was placed at 30°C and 150 r / min for 72 h of ammonium chloride stress / induction culture.
[0042] (3) Extraction of extracellular polymers: Take 30 mL of the bacterial solution after stress / induction culture in a centrifuge tube, centrifuge it in a high-speed refrigerated centrifuge at 8000 r / min and 4°C for 10 min, discard the supernatant and retain the bacteria; then wash the bacteria with 30 mL of 0.9% NaCl solution, centrifuge it again under the same conditions for 10 min, discard the supernatant and retain the bacteria. Repeat this washing process twice to wash away the Starkey medium and ammonium chloride remaining on the bacteria. Then use the NaOH method to extract extracellular polymers. When extracting, first wash the bacteria with 10 mL of 0.9% NaCl solution, then add 0.5 mL of 1.00 mol / L NaOH solution to the washed bacteria, shake well and place it in a 4°C refrigerator for 3 h. Then centrifuge it in a high-speed refrigerated centrifuge at 12000 r / min and 4°C for 20 min to extract extracellular polymers. The extracted extracellular polymers were filtered with a 0.45 μm cellulose acetate filter membrane, and then placed in a 4000 Da dialysis bag for 24 hours. The dialyzed extracellular polymers were stored at -20°C to obtain the extracellular polymers without the bacterial bodies. In addition, the bacterial bodies were retained and dried to a constant weight.
[0043] For comparison with ammonium chloride, this example also prepared extracellular polymers produced by Desulfovibrio desulfuricans subsp. desulfuricans under the stress / induction conditions of ammonium oxalate (stress / induction concentration of 1.6 g / L) and ammonium bicarbonate (stress / induction concentration of 1.6 g / L).
[0044] (4) Determination of the main components of extracellular polymers: The contents of protein, polysaccharide, and nucleic acid were determined by the Coomassie brilliant blue method, the sulfuric acid-anthrone method, and the diphenylamine method, respectively. The sum of the three was the extracellular polymer yield, expressed in mg / g EPS.
[0045] Figure 1 The results showed that the protein content of extracellular polymers was the highest when 2.0 g / L ammonium chloride was added, reaching 488.06 mg / g, which was higher than other ammonium salts (ammonium oxalate was 448.11 mg / g, ammonium bicarbonate was 431.71 mg / g), and increased by 56.20% to 76.58% compared with before stress / induction. The change trend of glucose in other components was not obvious, while the content of extracellular polymer nucleic acid under ammonium chloride stress / induction reached 143.55 mg / g, which was much higher than other ammonium salts (ammonium oxalate was 96.85 mg / g, ammonium bicarbonate was 86.07 mg / g), indicating that the stress / induction effect of ammonium chloride was better than that of ammonium oxalate and ammonium bicarbonate.
[0046] Example 2: Ammonium-induced synthesis of lead sulfide quantum dots mediated by extracellular polymers
[0047] Prepare 0.10 mol / L lead ion solution (precursor is lead nitrate, solvent is water), take 10 mL and dispense it into a 50 mL conical flask, then add 1.00 mg of the extracellular polymers extracted before and after ammonium salt stress / induction in Example 1, and add pure water to make up to 20 mL.
[0048] The mixture was placed in a constant temperature shaker at 150r / min and 30°C for 2h of oscillation adsorption to allow it to be fully adsorbed. The mixture was then transferred to a 4000Da dialysis bag and dialyzed in 200mL of ultrapure water for 12h to remove excess lead ions. The dialyzed mixture was then pipetted into a conical flask and 10mL of 0.03mol / L sulfide ion solution (the precursor is sodium sulfide and the solvent is water) was slowly added dropwise. After the mixture was allowed to stand for 30min, it was centrifuged at 4°C and 5000r / min for 10min to facilitate the collection of the synthesized lead sulfide quantum dots. The obtained lead sulfide quantum dots were washed twice with ultrapure water and anhydrous ethanol, respectively, and dried at 65°C to constant weight, and their spectral and structural properties were measured.
[0049] In addition, chemically synthesized lead sulfide was also prepared as a control, that is, 0.10 mol / L lead ion solution and 0.03 mol / L sulfide ion solution were directly mixed in equal volumes, and the subsequent standing, centrifugation, washing and drying steps were consistent with the above.
[0050] The free lead concentration in the ultrapure water outside the dialysate after 12 hours of dialysis was measured by atomic absorption spectrometry, and the yield and production of lead sulfide quantum dots were calculated. Figure 2It showed that the yield of lead sulfide quantum dots per unit extracellular polymer under the induction of ammonium chloride was 17.45 g / g EPS, which was 51.74% higher than that before induction, much higher than that of other ammonium salts (ammonium oxalate and ammonium bicarbonate); the yield of lead sulfide quantum dots per unit strain under the induction of ammonium chloride, ammonium oxalate and ammonium bicarbonate were 12.50 g / g biomass, 4.88 g / g biomass and 4.14 g / g biomass, respectively, which were 51.65% to 357.88% higher than that before induction.
[0051] Figure 3 The Fourier transform infrared spectrum results show that at 3422cm -1 The peak at 2920 cm corresponds to the stretching vibration of OH groups in intermolecular and intramolecular hydrogen bonds and NH groups in proteins; -1 The peak at 2858 cm is attributed to the stretching vibration of -SH; -1 The peak at 1636 cm represents the CH absorption of polysaccharide; -1 The peak at 1383 cm is related to the amide I band and is attributed to the vibration of the C=O bond of the secondary protein β structure; -1 The peak at corresponds to the C==O symmetric stretching of COO- in the presence of uronic acid. The existence of these absorption peaks indicates the role of protein, and the Starkey medium used in the early stage does not contain protein, which preliminarily proves that the protein on the surface of quantum dots is produced by the microorganism itself.
[0052] Figure 4 The high-resolution transmission electron microscopy and particle size distribution results show that the lead sulfide quantum dots synthesized in the ammonium chloride induction system are evenly distributed, with an average particle size of 7.54±1.26nm, mainly distributed in 7.00~8.00nm (about 36.00%), and the particle size of the obtained lead sulfide quantum dots is less than 20nm, so the synthesized lead sulfide particles belong to quantum dots. In the lattice spacing image, it can be observed that the product has a high degree of crystallinity, and it can be observed that the lattice spacing related to the (200) plane is 0.311mm.
[0053] Figure 5 The circular rings in the selected area electron diffraction pattern indicate that the biosynthesized lead sulfide quantum dots are polydisperse in particle size, and the concentric rings with bright spots confirm the crystalline nature of the lead sulfide quantum dots. In addition, the diffraction rings in the spectrum correspond to the crystal planes (111), (200), (220), (311), (220), (400), (331), (420) and (422), respectively, which can determine that the obtained product is a cubic phase of lead sulfide quantum dots with good properties of stable crystal phase.
[0054] Figure 6The nitrogen adsorption / desorption curves show that the adsorption isotherms of lead sulfide all belong to type IV of the IUPAC classification, among which chemically synthesized lead sulfide has an H1 type hysteresis loop, and the lead sulfide quantum dots synthesized by extracellular polymers have an H2(b) type hysteresis loop, which is usually due to the agglomeration of approximately spherical particles. It can be found in the pore size distribution diagram that the pore size distribution curves of the samples are all concentrated in the mesoporous region (2 to 50 nm). The lead sulfide quantum dots synthesized under the mediation of extracellular polymers have a larger specific surface area and a smaller average pore size than chemically synthesized lead sulfide. The specific surface area ranges from 37.9978 m 2 ·g -1 Increased to 60.0161m 2 ·g -1 , which gives the catalyst more active sites and enhances the adsorption capacity of the material. It is speculated that extracellular polymer-mediated synthesis promotes the catalytic performance of lead sulfide quantum dots.
[0055] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. A method for synthesizing lead sulfide quantum dots mediated by extracellular polymers, characterized in that: The following steps are involved: S1. Cultivate Desulfovibrio desulfuricans subsp. desulfuricans by ammonium stress / induction and extract extracellular polymers; S2, mixing the extracellular polymers of S1 with the lead ion solution, and performing dialysis after sufficient adsorption to remove excess lead ions; S3. After dialysis, sulfide ion solution is added, and the synthesized lead sulfide quantum dots are collected by centrifugation after standing.
2. The method for synthesizing lead sulfide quantum dots mediated by extracellular polymers according to claim 1, characterized in that: S1 specifically comprises: inoculating Desulfovibrio desulfuricans subsp. desulfuricans into Starkey medium containing ammonium salts, and after stress / induced culture, extracting the extracellular polymers produced by Desulfovibrio desulfuricans subsp. desulfuricans by using NaOH method.
3. The method for synthesizing lead sulfide quantum dots mediated by extracellular polymers according to claim 2, characterized in that: The concentration of the ammonium salt in the Starkey medium is 1.2-2.4 g / L, and the ammonium salt includes at least one of ammonium chloride, ammonium oxalate and ammonium bicarbonate.
4. The method for synthesizing lead sulfide quantum dots mediated by extracellular polymers according to claim 1 or 2, characterized in that: The stress / induction culture is carried out in a shaking culture mode, wherein the shaking culture temperature is 25-35° C., the time is 60-84 hours, and the shaking speed is 120-180 r / min.
5. The method for synthesizing lead sulfide quantum dots mediated by extracellular polymers according to claim 1, characterized in that: In S2, the mass volume ratio of extracellular polymers to lead ion solution is 1:1-5.
6. The method for synthesizing lead sulfide quantum dots mediated by extracellular polymers according to claim 1, characterized in that: In S2, the adsorption is carried out on a shaker at 25-35°C and a shaking speed of 120-180 r / min for 1-3 hours.
7. The method for synthesizing lead sulfide quantum dots mediated by extracellular polymers according to claim 1, characterized in that: In terms of the dosage of the sulfide ion solution and the lead ion solution, the molar ratio of the sulfide ion to the lead ion is 1:2-5.
8. The method for synthesizing lead sulfide quantum dots mediated by extracellular polymers according to claim 1, characterized in that: In the lead ion solution, the source of lead ions includes at least one of Pb(NO3)2, PbCl2 and PbSO4; the source of sulfide ions in the sulfide ion solution is sodium sulfide.
9. The method for synthesizing lead sulfide quantum dots mediated by extracellular polymers according to claim 1, characterized in that: In S3, the standing time is not less than 30 minutes.
10. Lead sulfide quantum dots synthesized by the method described in any one of claims 1 to 9.